Study on the mechanical properties of unloaded damage sandstone under dry-wet and freeze-thaw cycling conditions. - Wenrui Wang; Xingzhou Chen; Lili Chen; Sheng Gong; Zhenkun Su (PLoS ONE)
Understanding he impact of dry-wet and freeze-thaw cycles on the mechanical properties of unloaded damaged rock masses in reservoir bank slopes is crucial for revealing the deformation and failure mechanisms in artificially excavated slope rock masses within fluctuation zones. To address, the study focuses on unloaded damaged samples subjected to excavation disturbances, conducting various cycles of dry-wet and freeze-thaw treatment along with uniaxial and triaxial re-loading tests. A damage statistical constitutive model was established based on the experimental results and validated using numerical simulation methods. The results indicate: (1) The mechanical properties of sandstone, which has incurred damage and is not under load, are significantly impacted by cycles of drying-wetting and freezing-thawing. As the number of these environmental cycles increases, a descending trend becomes apparent in the stress-strain curve profile. This shift coincides with an increase in pore compaction strain as well as plastic strain values; meanwhile, peak strength experiences a sharp decline initially but subsequently moderates to more gradual reductions.; (2) The elastic modulus, cohesion, and friction angle all show a similar trend of attenuation, with the most severe degradation occurring after the first cycle and then gradually diminishing, particularly with the elastic modulus; (3) The uniaxial failure of the unloaded damaged samples is primarily brittle, with spalling and buckling becoming more pronounced with increasing cycles, while triaxial failure exhibits certain plastic characteristics that develop more with further cycling. As the frequency of dry-wet and freeze-thaw cycles rises, there is a corresponding increase in the number of fractures observed at the point of sample failure.